The cisplatin-induced lncRNA PANDAR dictates the chemoresistance of ovarian cancer via regulating SFRS2-mediated p53 phosphorylation. Issue 11 (November 2018) - Wang, Hao; Fang, Lei; Jiang, Jing; Kuang, Ye; Wang, Beidi; Shang, Xiumin; Han, Peilin; Li, Yue; Liu, Meimei; Zhang, Zongfeng; Li, Peiling
Abstract As a component of p53-dependent lncRNA (long non-coding RNA), PANDAR (the promoter of CDKN1A antisense DNA damage activated RNA) participates in the epigenetic regulation in human cancer. However, the involvement ofPANDAR in cancer chemoresistance is unknown. In this study, we report thatPANDAR serves as a negative regulator of cisplatin sensitivity in human ovarian cancer viaPANDAR -SRFS2-p53 feedback regulation in nuclear. Our data showed that among the drugs commonly used in ovarian cancer therapy, cisplatin induces higher levels ofPANDAR compared with doxorubicin and paclitaxel. We also proved thatPANDAR exhibited higher expression in cisplatin-resistant ovarian cancer tissues and cells, compared with cisplatin-sensitive ones, and this expression pattern depends on wild-type p53 (wt-p53), not mutant-p53 (mt-p53). In vitro and in vivo, PANDAR overexpression improved cell survival rate and tumor growth in response to cisplatin, while depletion ofPANDAR leads to a reduced tumor growth. Further investigation revealed thatPANDAR -reduced cisplatin sensitivity was likely or partly due to thePANDAR -binding protein SFRS2 (arginine/serine-rich 2), a splicing factor with the ability to negative regulate p53 and its phosphorylation at Serine 15 (Ser15). This feedback regulation ofPANDAR –SFRS2–p53 leads to a reduced transactivation of p53-related pro-apoptotic genes, such as PUMA (p53-upregulated modulator of apoptosis). In addition, in platinum-treated patients with relapsed ovarian cancer, resistant period was positively correlated with the expression ofPANDAR and SFRS2, and inversely associated with expression of p53-Ser15 and PUMA in these clinical tissues. Last but not least, the role ofPANDAR in chemoresistance was confirmed in patients with ovarian cancer. These findings reveal a novel regulatory maneuver of cancer cells in response to chemostress, and might shed light on overcoming cisplatin resistance in ovarian cancer.